OTORITAS FATWA MAJELIS ULAMA INDONESIA TENTANG UANG PANAI’ TELAAH SIYASAH SYAR’IYYAH DI KOTA MAKASSSAR - Rahman, Nurfadillah; Hasan, Hamzah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This research aims to find out how the Fatwa Authority of the Indonesian Ulema Council regarding Panai Money has studied Siyasah Syar'iyyah in Makasssar City. The main problem is divided into several sub-problems, namely: What are the legal rules for the Indonesian MUI fatwa regarding Panai money and how to implement the MUI fatwa regarding Panai money? Study the Siyasah Syariyyah. The research method used is qualitative research with data collection methods in the form of observation, interviews, documentation and reference tracking. The results of this research show that the MUI Fatwa Legal Rules regarding Uang Panai' are that the MUI Fatwa Legal Rules state that panai money is fine but does not make it difficult for men to get involved in it. Even though there is no Uang Panai elsewhere, the MUI respects the Uang Panai tradition in South Sulawesi. MUI does not prohibit, reject, or continue to tolerate this tradition so that it has become the custom of the Makassar Bugis community. MUI emphasized that many young people end up choosing not to get married not because of this tradition, but because it is difficult and requires more money than men can afford. The Bugis in society accept the validity of panai money and anticipate that the money will be changed according to the talents of the prospective bride and groom. (The man who wants to ask questions). Implementation of the MUI Fatwa regarding Uang Panai, which states that because Uang Panai has the power to issue infaq, it is preferred if it is a custom in Bugis marriages. In addition, it is very important that Uang Panai is resolved peacefully to prevent the development of tabzir, israf (waste) and hedonistic styles. For the legal requirements of panai money, the custom was basically accepted during that time. Basically, these practices are legal as long as they comply with sharia standards. Therefore, Uang Panai is subject to Sharia law, including allowing marriage and not oppressing men. Respect women, be trustworthy, and avoid subsequent manipulative behavior.